Adaptation of Traditional Festivals to Natural Resources Conservation Education: Lessons from Osun-Osogbo and Argungun Fishing Festivals in Nigeria - Olatumile, Adekunle (American Economic & Social Review, 2019)
Africa has been tagged a festival continent as year in year out, towns and villages witness cultural festivals throughout the year. These festivals are mostly concerned with resources conservation and utilization. The adoption of Western Model of conserving biodiversity in the trickle-down fashion has failed to yield reasonable result; whereas traditional festivals epitomize indigenous people’s respect and reverence for, and pragmatic understanding of, their natural environment. The quest of conserving biodiversity for sustainable development therefore calls for the integration of traditional festivals in sustainable resource management framework. In spite of the invaluable potentials of traditional festivals in biodiversity conservation as an indigenous resource management system, it has not been given a prominent place in the modern day scientific resource management framework. Using ethnographic research design, the paper exploits the natural resources conservation potentials of Osun-Osogbo and Argungun fishing festivals in Nigeria. Data are collected from archival, ethnographic and internet materials, as well as text books, pictures and information through interviews and observations. The paper presents an analysis of ways through which policy frameworks can benefit from festivals and how a wide audience can be reached with biodiversity conservation messages for the purpose of creating awareness. The paper develops a framework for ecosystem based adaptation, using indigenous festivals for the purpose of replicating it in every other community where such festivals do not exist and integrating it in festivals that are not based on natural resource conservation.